Oyster Mushroom’s Greenhouse Remote Monitoring System Based on Raspberry PI - -, Martanto; Yustia, Elisabet (Institut Teknologi Dirgantara Adisutjipto, 2018)
In the agricultural sector there are many mushroom farmers who do manual cultivation. Environmental factors that influence the growth of oyster mushrooms include temperature and humidity. This system was made to maintain the stability of temperature and humidity in oyster mushrooms’ greenhouse remotely. Communication of remote data exchange between Raspberry-Pi and Zelio using TCP/IP networks was successfully carried out. The system managed to run the features in the setting menu which is able to set the temperature and humidity set point values, set the on/off condition of the actuators, display the local system set point and set the on/off condition of the enable button in the GUI. Temperature and humidity values, and actuator status can displayed in monitoring menu. In the logging menu, the data was saved in csv format. Automatic file naming based on date was successfully done, the csv file was successfully opened and displayed in graphical plot.